Costs of immune responses are related to host body size and lifespan. Issue 5 (3rd August 2017) - Brace, Amber J.; Lajeunesse, Marc J.; Ardia, Daniel R.; Hawley, Dana M.; Adelman, James S.; Buchanan, Katherine L.; Fair, Jeanne M.; Grindstaff, Jennifer L.; Matson, Kevin D.; Martin, Lynn B.
GRAPHICAL ABSTRACT: There has been a growing interest in the possibility that the costs of immune activity have influenced the evolution of animal defenses against infection to a comparable degree as the benefits of defense. Here, we used meta‐analysis to probe how salient factors, namely body size and life‐history orientation, influence the magnitude of immune costs among animals. From 236 cost estimates among 39 species spanning nine orders of magnitude in body size, we found appreciable immune costs such that long‐lived species pay larger immune activation costs than short‐lived species, and small species pay higher immune activation costs than large species. Our work indicates that costs have indeed influenced the evolution of immune systems, results that have implications for zoonotic disease management as well as animal husbandry. Abstract: A central assumption in ecological immunology is that immune responses are costly, with costs manifesting directly (e.g., increases in metabolic rate and increased amino acid usage) or as tradeoffs with other life processes (e.g., reduced growth and reproductive success). Across taxa, host longevity, timing of maturity, and reproductive effort affect the organization of immune systems. It is reasonable, therefore, to expect that these and related factors should also affect immune activation costs. Specifically, species that spread their breeding efforts over a long lifetime should experience lower immune costs than those that mature and breed quickly and die comparatively early. Likewise, body mass should affect immune costs, as body size affects the extent to which hosts are exposed to parasites as well as how hosts can combat infections (via its effects on metabolic rates and other factors). Here, we used phylogenetic meta‐regression to reveal that, in general, animals incur costs of immune activation, but small species that are relatively long‐lived incur the largest costs. These patterns probably arise because of the relative need for defense when infection risk is comparatively high and fitness can only be realized over a comparatively long period. However, given the diversity of species considered here and the overall modest effects of body mass and life history on immune costs, much more research is necessary before generalizations are appropriate.